2017
DOI: 10.1002/jbmr.3346
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Driving Heterotopic Ossification: Convergence of Genetically-Driven and Trauma-Driven Mechanisms

Abstract: We read with great interest the recent article in the Journal of Bone and Mineral Research by Convente and colleagues, "Depletion of mast cells and macrophages impairs heterotopic ossification in an Acvr1 R206H mouse model of fibrodysplasia ossificans progressiva." (1) This article reports that muscle injury caused by intramuscular injection of cardiotoxin from Naja mossambica mossambica venom into the Acvr1 R206H mouse causes the development of heterotopic ossifications (HO) at the injury site. They demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…Recent studies showed the role of immune response cells, especially monocytes/macrophages, at the early stages of trauma-induced HO development [ 6 ]. They confirm the importance of macrophages in the induction of neurogenic and genetic forms of HO [ 7 ]. Activated macrophages express osteoinductive signaling factors in the course of HO pathogenesis.…”
Section: Introductionsupporting
confidence: 69%
“…Recent studies showed the role of immune response cells, especially monocytes/macrophages, at the early stages of trauma-induced HO development [ 6 ]. They confirm the importance of macrophages in the induction of neurogenic and genetic forms of HO [ 7 ]. Activated macrophages express osteoinductive signaling factors in the course of HO pathogenesis.…”
Section: Introductionsupporting
confidence: 69%
“…In this model the combination of two injuries is necessary to trigger NHO development in the muscle: a severe lesion of the central nervous system such as a SCI in combination with a muscle injury (13). Development of NHO following spinal cord transection in this model was triggered by macrophages infiltrating damaged muscles exclusively in the context of a complete SCI (13, 14). More recently we established that the inflammatory cytokine oncostatin M (OSM) secreted in part by macrophages infiltrating the inflamed muscle contribute to both human and mouse NHO development (15).…”
Section: Introductionmentioning
confidence: 99%
“…The enhancing effect of CSF1R tyrosine kinase inhibitor GW2580 on NHO development was also surprising because CSF1R signaling is necessary to maintain many tissue-resident macrophages and osteoclasts but dispensable to monocyte production in the bone marrow (39,40) although extra-physiological treatment with stable CSF-1 protein considerably enhances monopoiesis (29,40) . As macrophages are necessary to the development of SCI-induced NHO (8) as well as genetically-driven HO development in fibrodysplasia ossificans progressiva (17,41) , we anticipated that inhibition of CSF1R signaling would reduce NHO formation. The opposite effect that we observed on NHO formation in vivo may be due to the complex function of CSF-1 on macrophage biology.…”
Section: Discussionmentioning
confidence: 99%